Adsorption characteristics of the carbonaceous adsorbents for organic compounds in a model exhaust gas from thermal treatment processing. (4th May 2022) - Kawamoto, Katsuya
ABSTRACT: This study investigated the adsorption characteristics of the carbonaceous adsorbents for organic compounds in gas to gain technical knowledge useful for the appropriate operation and management of the incineration plants and industrial heat treatment facilities. The experiments in the study were performed using a dynamic method, employing a small column packed with test adsorbent, into which flowed the model gas, primarily over a temperature range of 150°C to 190°C. Three activated carbon materials and an activated coke were used, with specific surface areas ranging from 250 to 1, 100 m 2 /g-adsorbent. Organic components in the gas were produced and supplied at a concentration of tens of mg/m 3, and gaseous mercury was supplied at a concentration of around 100 μg/m 3 . The experimental results showed the following: 1) The adsorption capacity of every carbonaceous material for organic vapor decreased with increasing temperature, with roughly a three-fold difference in the capacity, between 150°C and 190°C in the dry gas. The equilibrium adsorption amount of benzene could be estimated based on the specific surface area of the adsorbent. 2) Gas moisture reduced the equilibrium adsorption amount of adsorbates by about half. 3) The estimation of the treatment performance for actual adsorption processing suggested the possibility of decreased removal efficiency at higher temperatures above 175°C. Overall, the precise process design should be made based on future practical studies. Implications : Adsorptive characteristics of activated carbon materials were examined for benzene and chlorobenzene in gas within the temperature range of 150°C to 190°C. The adsorption amount of benzene at high temperature and low concentration range below 20 ppm was in the range of 10 3 to 10 4 mg/kg-adsorbent. There was a clear difference between the adsorption parameters of activated carbon and coke for the benzene adsorption, depending on their specific surface area values and other factors.